Interrelación entre visión externa y visión interna en la poesía de José Ángel Valente - Aguirre Martínez, Guillermo (El Colegio de México, 2014)
A phenomenological study on José Ángel Valente’s poetry will allow us to join a material level with a spiritual one. In view of this work, the bestoption is to study the eye’s double function –inner and outer vision–.In this way, the poetic universe, shown as a whole, reveals the mysticalnature of Valente’s creation.The phenomenological study works as a bridge between two differentrealities, and consequently turns all different poetic images intocomplementary factors. This paper links all those different poetry levelswith the purpose of understanding Valente’s work as an integratedwhole.